Transcriptional Activities of the Microbial Consortium Living with the Marine Nitrogen-Fixing Cyanobacterium Trichodesmium Reveal Potential Roles in Community-Level Nitrogen Cycling - Lee, Michael D. (Appl Environ Microbiol, 2017)
Trichodesmium is a globally distributed cyanobacterium whose nitrogen-fixing capability fuels primary production in warm oligotrophic oceans. Like many photoautotrophs, Trichodesmium serves as a host to various other microorganisms, yet little is known about how this associated community modulates fluxes of environmentally relevant chemical species into and out of the supraorganismal structure. Here, we utilized metatranscriptomics to examine gene expression activities of microbial communities associated with Trichodesmium erythraeum (strain IMS101) using laboratory-maintained enrichment cultures that have previously been shown to harbor microbial communities similar to those of natural populations. In enrichments maintained under two distinct CO(2) concentrations for ∼8 years, the community transcriptional profiles were found to be specific to the treatment, demonstrating a restructuring of overall gene expression had occurred. Some of this restructuring involved significant increases in community respiration-related transcripts under elevated CO(2), potentially facilitating the corresponding measured increases in host nitrogen fixation rates. Particularly of note, in both treatments, community transcripts involved in the reduction of nitrate, nitrite, and nitrous oxide were detected, suggesting the associated organisms may play a role in colony-level nitrogen cycling. Lastly, a taxon-specific analysis revealed distinct ecological niches of consistently cooccurring major taxa that may enable, or even encourage, the stable cohabitation of a diverse community within Trichodesmium consortia. IMPORTANCE Trichodesmium is a genus of globally distributed, nitrogen-fixing marine cyanobacteria. As a source of new nitrogen in otherwise nitrogen-deficient systems, these organisms help fuel carbon fixation carried out by other more abundant photoautotrophs and thereby have significant roles in global nitrogen and carbon cycling. Members of the Trichodesmium genus tend to form large macroscopic colonies that appear to perpetually host an association of diverse interacting microbes distinct from the surrounding seawater, potentially making the entire assemblage a unique miniature ecosystem. Since its first successful cultivation in the early 1990s, there have been questions about the potential interdependencies between Trichodesmium and its associated microbial community and whether the host's seemingly enigmatic nitrogen fixation schema somehow involved or benefited from its epibionts. Here, we revisit these old questions with new technology and investigate gene expression activities of microbial communities living in association with Trichodesmium.